Effectiveness of School Operational Assistance Fund Management in Improving Learning Quality - H. Soro , Suharyanto; Ambarawati, Nina; Ratnawati, Ratnawati (Civiliza Publishing, Indonesia., 2025)
School operational funds are one of the supporting elements in creating quality education, especially in the context of financing. The realization of this assistance fund is an obstacle because the needs and costs are not covered. This study aims to find the effectiveness of the management of School Operational Assistance Funds (BOS) at SMP Negeri 3 Cipatat in order to improve the quality of learning. This study uses a case study approach with data collection methods through observation, interviews, and documentation studies. The results of the study show that (10 BOS Fund Management at SMP Negeri 3 Cipatat has been carried out in a participatory, transparent, and accountable manner; (2) Teachers are involved in the preparation of activity plans through deliberation forums and ARKAS meetings, so that the needs of learning and school operations can be accommodated effectively; (3) The implementation of BOS Funds has been proven to support various important aspects, such as increasing access to education, procurement of digital learning media, extracurricular activities, maintenance of facilities and infrastructure, and increasing teacher competence through In House Training (IHT) activities. The conclusion of this study is that the management of BOS Funds at SMP Negeri 3 Cipatat has been effective in supporting the improvement of the quality of learning and strengthening school governance.